Andrea del Sarto : splendor and renewal in the Renaissance altarpiece - Cody, Steven J. (Brill's studies in intellectual history, 2020)
"Over the course of his career, Andrea del Sarto (1486-1530) created altarpieces rich in theological complexity, elegant in formal execution, and dazzlingly brilliant in chromatic impact. This book investigates the spiritual dimensions of those works, focusing on six highly-significant panels. According to Steven J. Cody, the beauty and splendor of Andrea's paintings speak to a profound engagement with Christian theories of spiritual renewal-an engagement that only intensified as Andrea matured into one of the most admired artists of his time. From this perspective, Andrea del Sarto - Splendor and Renewal in the Renaissance Altarpiece not only shines new light on a painter who has long deserved more scholarly attention; it also offers up fresh insights regarding the Renaissance altarpiece itself"--